Creativity at the margins : the performances of an artist in the Venda region of South Africa - Kaplan, Oren Mark (My University, 2014)
Vho-Ratshilumela Samson Mudzunga staged three performances between June 1996 and March 1997 in the far northern Venda region of South Africa. The performances included dramatic enactments which were based on mimetic recreations of, what he termed traditional, rites of passage. Thus he staged his own funeral in June 1996 and a traditional Venda wedding in March 1997. He also held a performance at Lake Fundudzi in September 1996. In these performances Vho-Mudzunga acted out scenarios which slid between representations of ritual practices and acts intended to provoke a sense of wonder. In the process of planning and executing the performances Vho-Mudzunga generated, through symbols, conflicts and narratives, ‘images’ o f the patterns of transgressive, autochthonous and extra-local power. The local context, in an out-of-the-way place in the South African state, proved to be a heteregenous, ensemble o f paradoxical relations o f power. In a typical mode of contradiction that flowed from this heterogeneity and characterized his actions, Vho-Mudzunga both challenged and perpetuated forms of authority and influence. The penetration of the art-market and the discourse and practice of ‘Art’ into the Venda region in 1985, was a crucial context for understanding Vho-Mudzunga’s contradictory strategies, and, more generally the conditions of marginality which structured experience and identity at the South African periphery. Discourses and practices, emanating from powerful centres, excluded and defined the Venda region and its inhabitants in a way that severely disrupted their experiences of space, history and a sense of self or personhood. The entrance of the art-market into the Venda region in 1985 enabled Vho-Mudzunga, as an artist, to gain access to the material and symbolic power of the prestigious metropolitan centre. The performances were Vho-Mudzunga’s way of engaging and addressing the disruptive effects of marginality. They re-dressed his personal and social experiences o f dislocation and reconstructed space, history and personhood in an idealized image under his control. 1 argue that post-apartheid South Africa provided new and specific conditions for marginal peoples to engage the centre.
Thesis (M.A.)--University of the Witwatersrand, Faculty of Arts, 1998.